Oral Health, Temporomandibular Disorder, and Masticatory Performance in Patients with Charcot-Marie-Tooth Type 2 - Rejane L. S. Rezende; Leonardo R. Bonjardim; Eduardo L. A. Neves; Lidiane C. L. Santos; Paula S. Nunes; Catarina A. Garcez; Cynthia C. Souza; Adriano A. S. Araújo (The Scientific World Journal)
Background. The aim of this study was to evaluate the oral health status of temporomandibular disorders (TMD) and bruxism, as well as to measure masticatory performance of subjects with Charcot-Marie-Tooth type 2 (CMT2). Methods and Results. The average number of decayed, missing, and filled teeth (DMFT) for both groups, control (CG) and CMT2, was considered low (CG = 2.46; CMT2 = 1.85, P=0.227). The OHIP-14 score was considered low (CG = 2.86, CMT2 = 5.83, P=0.899). The prevalence of self-reported TMD was 33.3% and 38.9% (P=0.718) in CG and CMT2 respectively and for self-reported bruxism was 4.8% (CG) and 22.2% (CMT2), without significant difference between groups (P=0.162). The most common clinical sign of TMD was masseter (CG = 38.1%; CMT2 = 66.7%) and temporalis (CG = 19.0%; GCMT2 = 33.3%) muscle pain. The geometric mean diameter (GMD) was not significantly different between groups (CG = 4369; CMT2 = 4627, P=0.157). Conclusion. We conclude that the CMT2 disease did not negatively have influence either on oral health status in the presence and severity of TMD and bruxism or on masticatory performance.